EFEKTIVITAS PROGRAM SEMUA IKUT BERGERAK BERSAMA MENANGANI STUNTING (SI BENING) DALAM UPAYA PENURUNAN STUNTING DI KELURAHAN TANJUNGMAS KECAMATAN SEMARANG UTARA - Afielia Firdaust, Pinkan; Maesaroh, Maesaroh; Widowati, Nina (Journal of Public Policy and Management Review, 2024)
The problem of stunting in Semarang City is still quite high, with a target of zero stunting by 2024 as a government effort to overcome this problem. In 2023, North Semarang Sub-district recorded the highest stunting rate in Semarang City with the highest rate in Tanjung Mas Village with 72 children. This study aims to analyse the effectiveness of the All Ikut Bergerak Bersama Menangani Stunting (Si Bening) Program in reducing stunting in Tanjung Mas Village, North Semarang District. Efforts to solve the problems and objectives of this study by using the theory of programme effectiveness according to Sutrisno, which measures five indicators: understanding of the programme, accuracy of targets, timeliness, achievement of goals, and real changes. This research uses a qualitative descriptive method, and the data in this research is obtained from primary and secondary data through observation, interviews and literature studies. The results showed that the effectiveness of the Si Bening programme in this location has not been maximised as seen from the indicators of understanding of the programme among mothers of stunting toddlers who have not been able to apply what the aims and objectives of this programme are. The program's goal of reducing stunting rates has been achieved but not maximised because there are still several obstacles from parents and toddlers themselves that make the 2024 zero stunting target in Semarang City not yet realised because it requires a long process.